2019
DOI: 10.3892/or.2019.7270
|View full text |Cite
|
Sign up to set email alerts
|

Emodin attenuates adenosine triphosphate‑induced pancreatic ductal cell injury in vitro via the inhibition of the P2X7/NLRP3 signaling pathway

Abstract: Acute pancreatitis (AP) is an inflammatory disease with high morbidity and mortality rates. Pancreatic ductal cells are the most susceptible of all cell types that are exposed to the noxious stimuli of pancreatitis. Our previous studies demonstrated that emodin, a natural product extracted from Rheum palmatum L., protected pancreatic acinar cells from injutyh due to its anti-inflammatory activity. In the present study, in order to investigate the protective effects and molecular mechanisms of action of emodin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 31 publications
1
19
0
1
Order By: Relevance
“…Feng et al treated acute pancreatitis (AP) rats with rhubarb decoction orally (150 mg/ kg) and found that rhubarb probably attenuated AP by inhibiting activation of MAPKs [49]. Our previous studies also proved that emodin alleviated AP via miRNA-30a-5p/HtrA serine peptidase 1/transforming growth factor-β (HTRA1/TGF-β) and purinergic receptor P2X, ligand-gated ion channel, 7/NLRP3 (P2X7/NLRP3) inflammatory signaling [50,51].…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…Feng et al treated acute pancreatitis (AP) rats with rhubarb decoction orally (150 mg/ kg) and found that rhubarb probably attenuated AP by inhibiting activation of MAPKs [49]. Our previous studies also proved that emodin alleviated AP via miRNA-30a-5p/HtrA serine peptidase 1/transforming growth factor-β (HTRA1/TGF-β) and purinergic receptor P2X, ligand-gated ion channel, 7/NLRP3 (P2X7/NLRP3) inflammatory signaling [50,51].…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…Diels could reduce the liberation of proinflammatory cytokines, including IL-1β, IL-6, TNF-alpha, and IL-33 ( Kim et al, 2018b ; Shen et al, 2019 ). They have an anti-inflammatory and analgesic effect ( Wei et al, 2016 ), induce cell proliferation ( Gundogdu et al, 2019 ), and protect cells from injuries ( Zhang et al, 2019b ). But, the activity of BO in anti-inflammation, analgesia, and promoting skin wound healing, and its specific mechanism are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al found that emodin (60 mg/kg) significantly inhibited the expression levels of P2X7 and NLRP3, thus delaying 5.0% sodium taurocholate-induced inflammasome activation and severe acute pancreatitis (SAP) progress in rats [ 46 ]. On the other hand, in an in vitro ATP‑injured model of human pancreatic ductal epithelial cell line (HPDE6‑C7), this protective activity of emodin against SAP was abrogated after pretreatment with P2X7 overexpression plasmid, which further verified that P2X7/NLRP3 signaling was the target of emodin on regulating inflammasome activation [ 47 ]. Moreover, a recent study revealed that emodin (25 mg/kg) protected against SAP-associated acute lung injury (ALI) in rats through the inhibition of NLRP3 inflammasome and uncovered a novel mechanism.…”
Section: Pharmacological Effects Of Emodinmentioning
confidence: 97%